2020
DOI: 10.1111/dme.14309
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study exploring the expectations of people living with type 1 diabetes regarding prospective use of a hybrid closed‐loop system

Abstract: Aim To identify the expectations of a diversified sample of informed adults with type 1 diabetes on their prospective use of a hybrid closed-loop system. Methods Semi-structured interviews were conducted with 16 adults with type 1 diabetes who shared their expectations on an experimental hybrid closed-loop system after receiving information on its design, functioning and capability. The sample had equal representation of genders and diabetes management methods and was diversified according to age, education an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…In addition to the clinical benefits of the Omnipod 5 described here, the system has been designed to meet the user's desire for convenience and confident diabetes management. 42 Although participants in this study were provided with a locked-down smartphone device with the Omnipod 5 mobile app, the commercially available system will also have the option to use a downloadable mobile app on the user's personal smartphone to control Pods. The ability to control devices from personal smartphones is a much-requested feature, which enables convenience and discreet insulin delivery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the clinical benefits of the Omnipod 5 described here, the system has been designed to meet the user's desire for convenience and confident diabetes management. 42 Although participants in this study were provided with a locked-down smartphone device with the Omnipod 5 mobile app, the commercially available system will also have the option to use a downloadable mobile app on the user's personal smartphone to control Pods. The ability to control devices from personal smartphones is a much-requested feature, which enables convenience and discreet insulin delivery.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to control devices from personal smartphones is a much-requested feature, which enables convenience and discreet insulin delivery. 42 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that improved glycemic control was already a standard expectation of an AP system, while a reduction in burden was suggested because it was less expected and still needed. A recent qualitative study of adults' expectations of hybrid closed‐loop systems prior to use similarly found that all participants expected the system to improve their glucose values, but fewer expected the system to improve their psychological well‐being 31 . Other research has also shown similar perspectives from participants, in which desired features were intended for benefit beyond glycemic outcomes 12 .…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, treatment satisfaction was increased with the automated insulin delivery system, in line with patients' expectations regarding the prospective use of automated insulin delivery systems. 23 The two large studies of the University of Cambridge and the University of Virginia algorithms included a review of data and adjustments of therapy parameters after 2 weeks of system usage. 8,10 Moreover, it has been reported that patients transitioning to the 670G system usually adjust their insulinto-carbohydrate ratios to be more aggressive by 15%-20%.…”
Section: Discussionmentioning
confidence: 99%